Assessment of CYP450 genetic variability effect on methadone dose and tolerance. (May 2014) - Tsai, Hui-Ju; Wang, Sheng-Chang; Liu, Sheng-Wen; Ho, Ing-Kang; Chang, Yao-Sheng; Tsai, Yu-Ting; Lin, Keh-Ming; Liu, Yu-Li
Aim: Methadone dose is related to treatment success in individuals under methadone maintenance treatment (MMT). We constructed a gene matrix using previously identified genetic polymorphisms in CYP450 and determined their genetic influence on methadone dose or tolerance.Materials & methods: The allelic combinations of CYP450 genetic variants (two from CYP2C19, four from CYP2B6 and five from CYP3A4 ) were analyzed in 366 MMT heroin dependent patients as possible determinants of methadone dose and tolerance using analysis of covariance.Results: Methadone dose (p = 0.007) and tolerance (p = 0.06) were mainly influenced by CYP2C19 gene dose. Moreover, dominant influence of the CYP2C19 gene dose on methadone dose and tolerance was only found among MMT patients with negative urine morphine test results, but not among those with positive results.Conclusion: The findings suggest that CYP2C19 gene dose may serve as a potential indicator for assessing methadone dose and tolerance in MMT patients. Original submitted 5 September 2013; Revision submitted 23 January 2014